Design of a Web-Based QR Code Attendance System with Real-Time Notifications at Darul Arqom Junior High School Karanganyar - Abid Nasiruddin; Wakhid Kurniawan (LPPM Universitas Bhinneka Nusantara, 2026)
The rapid development of information technology has encouraged educational institutions to implement digital transformation in administrative management, including student attendance systems in Islamic boarding schools. SMP Darul Arqom Karanganyar still uses a manual paper-based attendance system that often causes recording errors, delays in attendance recapitulation, difficulties in monitoring student attendance, potential data manipulation, and delays in delivering attendance information to parents. These problems indicate that the attendance management process is inefficient and requires a more integrated digital solution. This study aims to design and develop a web-based attendance system using QR Code technology integrated with real-time notifications to improve the efficiency, accuracy, and transparency of student attendance management. The novelty of this research lies in integrating QR Code-based attendance validation with automatic real-time notifications for parents in a system specifically designed for the Islamic boarding school environment. Unlike previous attendance applications that mainly focus on digital attendance recording, the proposed system emphasizes attendance transparency, fraud prevention, and direct communication between schools and parents. The system was developed using the Agile Development method through iterative sprint-based stages, including planning, design, development, testing, evaluation, and implementation. The system utilizes the CodeIgniter framework, MySQL database, and QR Code technology for attendance validation. The results show that the system accelerates the attendance process, minimizes fraudulent attendance practices, improves attendance data accuracy, and assists administrators in monitoring attendance data efficiently. In addition, the system increases information transparency through direct real-time notifications to parents. Therefore, the system can support administrative digitalization and student discipline management in Islamic boarding schools.